Pengaruh Metode Diskusi dalam Meningkatkan Pemahaman Konsep Aljabar di Kelas 8 Semester 1 pada SMPN Satu Atap 3 Wolomeze Tahun Pelajaran 2023/2024 - Fransiska Rheyneldis Rembo (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to improve the understanding of algebraic concepts among 8th-grade students through the discussion method. The research subjects were 30 students of SMPN Satap 3 Wolomeze. This classroom action research consisted of three cycles, each including planning, implementation, observation, and reflection. The results showed an increase in students' average scores from 60 (pre-cycle) to 85 (cycle 2). Student engagement also improved from 40% to 85%. The discussion method proved effective in enhancing the understanding of algebraic concepts, particularly in linear equations and factorization.